Advances in the Molecular Diagnosis of Hepatitis B Infection: Providing Insight into the Next Generation of Disease - Bayliss, Julianne; Nguyen, Tin; Lesmana, C. Rinaldi A.; Bowden, Scott; Revill, Peter (Seminars in Liver Disease, 2013)
Hepatitis B virus (HBV) infection continues to represent a significant health threat, affecting over 400 million people worldwide. Historically, the diagnosis and treatment of chronic hepatitis B (CHB) relied in detection of the hepatitis B surface antigen (HBsAg) and more recently realtime polymerase chain reaction (PCR) analysis. The advent of novel technologies and equipment for the identification and staging of the different stages of HBV infection has resulted in dramatic changes to patient monitoring and management. Through the use of rapid, quantitative HBsAg immunoassays, it is now possible to predict the likelihood of patient response to treatment as well as the clinical course of disease. Ultradeep sequencing technologies (also known as next-generation sequencing) overcome many of the traditional limitations associated with population-based sequencing approaches, and have provided significant insight into the viral response to therapeutic intervention and the molecular pathogenesis of CHB. The authors discuss recent developments in the molecular diagnosis of HBV infection, as well as potential advantages and caveats resultant of this rapid progression of technology.
Keywords: hepatitis B virus (HBV); chronic infection; diagnosis; hepatitis B surface antigen (HBsAg); next-generation sequencing